Amendments to Law of the Republic of Indonesia Number 40 of 1999 Concerning the Press: Between Needs and Obligations - Untung Sumarwan; Arief Hidayat; Lita Tyesta (Ikatan Sarjana Komunikasi Indonesia, 2023)
Amendments to the law, as a manifestation of legal politics designed to promote public contentment is inevitable. The theory of law stipulates the significance of developments that are deemed highly necessary. Problems arose when the government of Indonesia's agenda to amend Law Number 40 of 1999 concerning the press raised concerns about the threat of oppression in the media. This study aims to determine the urgency of amending the Press Law to realize press freedom in Indonesia. This study used a qualitative method through literature studies and interviews with practitioners. The results of this study showed that Law Number 40 of 1999 concerning the Press is a legitimate tool for press freedom at this time. It can be stated that the substance of Law No. 40 of 1999 regarding the Press is still relatively accommodating democracy in terms of ensuring freedom of opinion as human rights. However, the dominance of the media company as the capital owner will limit press freedom, necessitating a structure that can finally separate the company from the press product. In the end, the success of Law Number 40 of 1999 pertaining to the Press must be evaluated based on institutions, enforcement, and the legal culture of the society.